2012
DOI: 10.1038/srep00830
|View full text |Cite
|
Sign up to set email alerts
|

High temperatures-related elderly mortality varied greatly from year to year: important information for heat-warning systems

Abstract: We examined the variation in association between high temperatures and elderly mortality (age ≥ 75 years) from year to year in 83 US cities between 1987 and 2000. We used a Poisson regression model and decomposed the mortality risk for high temperatures into: a “main effect” due to high temperatures using lagged non-linear function, and an “added effect” due to consecutive high temperature days. We pooled yearly effects across both regional and national levels. The high temperature effects (both main and added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 40 publications
2
47
0
1
Order By: Relevance
“…Other studies have observed higher risks among the elderly due to the decreased thermoregulatory capacity when a person ages [20,29]. Factors such as dehydration affect the elderly through decreased sweat production and reduced direct loss of skin warmth, thereby decreasing the thermoregulation and thermal homeostasis [30,31]. Although the elderly people have greater effects estimates compared to the other age-specific risk groups, as seen in Table 5, the estimates were not significant.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have observed higher risks among the elderly due to the decreased thermoregulatory capacity when a person ages [20,29]. Factors such as dehydration affect the elderly through decreased sweat production and reduced direct loss of skin warmth, thereby decreasing the thermoregulation and thermal homeostasis [30,31]. Although the elderly people have greater effects estimates compared to the other age-specific risk groups, as seen in Table 5, the estimates were not significant.…”
Section: Discussionmentioning
confidence: 91%
“…New knowledge about the human response to heat could lead to more efficient allocation of resources associated with the activation of heat emergency management protocols as well as those associated with longer-term mitigation and adaptation strategies. Recent research has contributed to increased awareness of geographic variability in the response to heat within large metropolitan areas (e.g., Vaneckova et al 2010 and of intra-annual variability in the metropolitan aggregate-scale response to heat (e.g., Guo et al 2012). But little effort has been directed at the intersection of these sources of variability-exploring how the intra-city human response to heat, in particular morbidity and mortality, changes from one year to another.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the heat-mortality response varies across time (e.g., , Rocklov et al 2009, Guo et al 2012. Although considerable debate continues regarding future climate change and population adaptation, the increase in temperatures in recent years combined with urban heat island impacts has resulted in individuals being more frequently exposed to thermally stressful conditions in some locations (Arnfield et al 2002, Wilby et al 2003.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations